Determinants of Mortality in Patients with Dengue Fever in a Tertiary Care Hospital of Dhaka City (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Dengue fever, an endemic mosquito-borne viral disease, poses a significant health challenge  globally, especially in tropical regions like Bangladesh. The country has witnessed an alarming rise in dengue-related  mortality, particularly since 2021, culminating in a record high in 2023, necessitating an investigation into the determinants  of dengue mortality to improve patient outcomes. This study aims to identify demographic, clinical, and biochemical factors  associated with mortality in patients diagnosed with dengue fever in a tertiary care hospital in Dhaka City.  Methods: This case-control study was conducted at Aalok Hospital in Mirpur, Dhaka, focusing on patients aged 18 years and  older who were admitted during the dengue outbreak of 2024. The study included 123 participants, comprising 7 cases  (patients who died from dengue) and 116 controls (patients who survived) of the disease. Inclusion criteria required a  confirmed diagnosis of dengue fever or dengue hemorrhagic fever based on clinical and laboratory findings, including positive  dengue NS1 antigen or IgM antibodies. Patients with severe comorbidities and those with a recent history of dengue infection  were excluded to avoid bias. Data were collected on demographic, socioeconomic, clinical, and biochemical factors, suspected  to be associated with the death (the outcome variable) of dengue patients. All the suspected exposure variables were then  compared between case and control groups to see whether they were associated with the outcome fo interest.  Result: The study found that the mean age of the cases was significantly higher than that of the controls. A notable proportion  of both groups belonged to middle- and upper-middle-class families, with no significant difference in socioeconomic status.  However, service-holders carried a higher mortality risk compared to other occupants. Clinical symptoms such as hypotension,  retro-orbital pain, and restlessness were significantly more common among the case group. Furthermore, the cases  demonstrated a higher incidence of altered sensorium, ascites, and electrolyte imbalances. Notably, 57% of the cases  exhibited acute liver injury (ALT > 200 U/L), compared to only 11.2% of the controls. Thrombocytopenia and gastrointestinal  bleeding manifestations were more prevalent in the case group. Additionally, complications like shock syndrome and  disseminated intravascular coagulation (DIC) were significantly associated with mortality.  Conclusion: Addressing the multifaceted determinants of dengue mortality is crucial for improving patient outcomes and  reducing the burden of this disease in Bangladesh. A comprehensive, concerted clinical management, is essential to combat  the rising dengue incidence and the mortality caused by it. Ibrahim Card Med J 2024; 14(1): 40-45